EVALUATION OF POLITICAL PERFORMANCE BUDGETING IN REGIONAL DEVELOPMENT POLICIES ON REFOCUSING COVID 19 IN TANJUNGPINANG - Irman, Irman; Darmawan, Eki (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2021)
During the Covid-19 pandemic, determining policies in the development sector greatly determines performance in government, both at the regional and central government levels. This paper focuses on performance evaluation in a political context on refocusing budgeting in handling Covid 19 in Tanjungpinang City in 2020. The research method is carried out with a qualitative approach which is a literature study by examining some secondary data. The secudender data obtained is relevant and then analyzed in depth against the main indicators of performance in public budgeting in the government system in Tanjungpinang City. The results of the analysis show that the performance evaluation in the Tanjungpinang City government shows that the influence on political performance is still very low in the quality of performance in the Tanjungpinang City government in public budgeting. In addition, the context in public budgeting should involve stakeholders in the form of collaborative governance so that political performance in budgeting in regional development provides a win-win solution in refucing the handling of COVID-19 in Tanjungpinang City